Стратегии развития розничных сетей в России - ШерешеваМарина Юрьевна; КотельниковаЗоя Владиславовна; РадаевВадим Валерьевич; ТретьякОльга Анатольевна (Экономическая социология, 2011)
Подробное описание в тексте